Objective features of international intergovernmental organizations - Щокін, Ю. В. (Problems of legality, 2013)
It has been carried out of analysis of international intergovernmental organizations’ main features, which distinguish them from other legal forms of interstate cooperation. The author‘s definition of «international intergovernmental organization» is proposed.